Q: Is 60 2x equals to 70 4x what is x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

60-2x = 70-4x 60-2x+2x = 70-4x+2x 60 = 70 +2x 60-70 = 70 + 2x - 70 -10 = 2x x = -10/2 = -5

4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y

x - 2x + 10 + 4x = 70 Combine like terms: 3x + 10 = 70 Subtract 10 from both sides: 3x = 60 Divided both sides by 3: x = 20

2x = 4x - 70; it is easiest to first get rid of a 2 factor, so x = 2x - 35. subtract 2x from both sides, getting -x = -35. multiply both sides by -1, getting x = 35. Then, to check, plug the numbers back in. 2(35) = 4(35) - 70; 70 = 70.

42 is 60% of 70

Related questions

60-2x = 70-4x 60-2x+2x = 70-4x+2x 60 = 70 +2x 60-70 = 70 + 2x - 70 -10 = 2x x = -10/2 = -5

4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y

x - 2x + 10 + 4x = 70 Combine like terms: 3x + 10 = 70 Subtract 10 from both sides: 3x = 60 Divided both sides by 3: x = 20

2x = 4x - 70; it is easiest to first get rid of a 2 factor, so x = 2x - 35. subtract 2x from both sides, getting -x = -35. multiply both sides by -1, getting x = 35. Then, to check, plug the numbers back in. 2(35) = 4(35) - 70; 70 = 70.

Let the number be x Then: x + 130 = 2x + 60 → 2x - x = 130 - 60 → x = 70 The number is 70.

42 is 60% of 70

4x-5y=20 x-3y=10 becomes x=3y-10 plug that into the first equation: 4(3y-10)-5y=20 12y-40-5y=20 7y=60 y=60/7 If x=3y-10, then x=3(60/7)-10 x=180/7 - 70/7 x=110/7

40

-10

i am guessing here that this is what you mean as it involves substitution: 2x-2y = 4 therefore -2y = 4 - 2x Sub the above line into the first equation gives: 13x - 2x +4 = 70 11x = 66 x=6 then sub in x 13(6) - 2y = 70 78 - 2y = 70 y=4 Yep, this is the exact same as simultaneous equations

Solve for what? Do you want to rearrange the equation for y to be a function of x? y = 70 - 4x Do you want to rearrange it as a function of y? x = (70 - y) / 4 You'll need to be more specific in exactly what you want done.

x = 6 and 2/7